Guidelines for Developing Digital Competency of Government Officials of The District Administration Office in Chumphon Province - Suaysom, Panthip; Anusonphat, Nalaumon (Journal of Human and Society, Sisaket Rajabhat University, 2024)
This research had objectives to 1) to study the level of digital competency of government officials at district administration offices in Chumphon Province; 2) to compare the digital competency of government officials at district administration offices in Chumphon Province; and 3) to find the guideline for developing digital competency of government officials in district administration offices in Chumphon Province. The sample of this research consisted of 100 government officials from district administration offices in Chumphon Province. The research tool is the questionnaire for interviewed to determine guideline for developing digital competency. The result of the research found out that the overall digital competency level of government officials was at a high level, which considered in individual aspects were, the aspect with the highest level was attribute ( = 4.51, S.D. = 0.52), followed by knowledge ( = 4.00, S.D. = 0.51), both at high levels. The skill had the lowest mean score ( = 3.95, S.D. = 0.41), at high level. For the guideline for enhancing digital competency was to change the thought of learning for new technologies, continuous training, and organizational support.